1979
DOI: 10.1042/bj1820811
|View full text |Cite
|
Sign up to set email alerts
|

Importance of mammalian nuclear-envelope nucleoside triphosphatase in nucleo-cytoplasmic transport of ribonucleoproteins

Abstract: The nucleoside triphosphate-stimulated efflux of RNA from isolated nuclei was studied under a range of conditions, and the effects of these conditions on the process were compared with the properties of the nucleoside triphosphatase located in the pore complex. A marked similarity between the rate of efflux and the rate of nucleoside triphosphate hydrolysis was apparent, in terms of substrate specificity, sensitivity to treatment with insolubilized trypsin, kinetics and the effects of increased ionic strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
49
2
2

Year Published

1980
1980
1997
1997

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 34 publications
5
49
2
2
Order By: Relevance
“…Investigations in my laboratory (Agutter et al, 1976(Agutter et al, , 1979b and by others (Clawson & Clawson et al, 1978) supported the fourth of these interpretations. More specifically, Agutter et al (1976, 1979b) have provided evidence that ATP hydrolysis occurs at an NTPase located in the nuclear-pore complex (Yasuzumi & Tsubo, 1966;Yasuzumi et al, 1967;Chardonnet & Dales, 1972;Franke, 1974), and that this event is necessary for RNA transport.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Investigations in my laboratory (Agutter et al, 1976(Agutter et al, , 1979b and by others (Clawson & Clawson et al, 1978) supported the fourth of these interpretations. More specifically, Agutter et al (1976, 1979b) have provided evidence that ATP hydrolysis occurs at an NTPase located in the nuclear-pore complex (Yasuzumi & Tsubo, 1966;Yasuzumi et al, 1967;Chardonnet & Dales, 1972;Franke, 1974), and that this event is necessary for RNA transport.…”
supporting
confidence: 62%
“…More specifically, Agutter et al (1976, 1979b) have provided evidence that ATP hydrolysis occurs at an NTPase located in the nuclear-pore complex (Yasuzumi & Tsubo, 1966;Yasuzumi et al, 1967;Chardonnet & Dales, 1972;Franke, 1974), and that this event is necessary for RNA transport. However, the findings of Agutter et al (1979b) and Clawson et al (1978) are not wholly consistent with one another. The main differences are that: (a) Clawson et al (1978) reported that ADP stimulated RNA release to a significant extent, but Agutter et al (1979b) were unable to repeat this observation; (b) Clawson et al (1978) found that pchloromercuribenzoate markedly stimulated RNA release in the presence of ATP, whereas Agutter et a!.…”
mentioning
confidence: 43%
“…The release of mRNA, unlike that of ribosomal RNA, is dependent on ATP hydrolysis. This is compatible with the requirement for polyadenylation in the processing of mRNA precursors [45] as well as the involvement of nuclear-porecomplex triphosphatase in the transport of mRNA as proposed by Clawson et al [46] and Agutter et al [47]. That RNA transport still occurs after treatment of nuclei with non-ionic detergent confirms the findings of Roy et al…”
Section: Discussionsupporting
confidence: 80%
“…[13], and suggests that nuclear membrane phospholipid is not rcquired, contrary to the conclusions of others [47,48]. The molecular hybridisation assays show that the transported poly(A)-rich R N A is a diverse mixture of RNA sequences which is similar to that expected for a population of newly transported mRNAs.…”
Section: Discussioncontrasting
confidence: 48%
“…In contrast to the nonhistone, actin or P-tubulin mRNA, all three histone mRNA studied (H4, H2B and H1) were released into the postnuclear supernatant also in the absence of nucleotides, although at lower rates (about 50% of that in the presence of ATP). Addition of inhibitors of the nuclear envelope NTPase, previously found to inhibit transport of poly(A)-rich mRNA [46], caused only a slight decrease in efflux of histone mRNA. A striking argument for an involvement of the NTPase in mRNA transport was the finding that ATP hydrolysis by this enzyme and RNA efflux display similar activation energies [48].…”
Section: Discussionmentioning
confidence: 99%